In vitro study on tooth enamel lesions related to whitening dentifrice - Danilo Barral de Araújo; Luciana Rodrigues Silva; Elisângela de Jesus Campos; Roberto Paulo Correia de Araújo (Wolters Kluwer Medknow Publications, 2011)
Background: The tooth whitening substances for extrinsic use that are available in Brazil contain hydrogen peroxide or carbamide peroxide. Several studies have attributed the appearance of lesions in the enamel morphology, including hypersensitivity, to these substances. Such lesions justify fluoride therapy and application of infrared lasers, among other procedures. However, there is no consensus among researchers regarding the relevance of the severity of lesions detected on the tooth surface. Objectives: The present study was carried out with an aim of evaluating in vitro the effects of the hydrogen peroxide, carbamide peroxide and sodium bicarbonate contained in dentifrice formulations, on human tooth enamel. Materials and Methods: After darkening process in laboratory, human premolars were brushed using dentifrice containing the two whitening substances (Rembrandt - carbamide peroxide and Mentadent - hydrogen peroxide) and the abrasive product (Colgate - sodium bicarbonate). The degree of specimen staining before and after this procedure was determined using spectrophotometry. Scanning electron microscopy (SEM) was used to obtain images, which were analyzed to show the nature of the lesions that appeared on the enamel surface. Results: The effectiveness of the whitening caused by hydrogen peroxide and carbamide peroxide and the abrasion caused by bicarbonate were confirmed, given that the treated test pieces returned to their original coloration. Based on SEM, evaluation of the enamel surfaces subjected to the test products showed that different types of morphologic lesions of varying severity appeared. Conclusions: Whitening dentifrice containing hydrogen peroxide and carbamide peroxide produced lesions on the enamel surface such that the greatest sequelae were associated with exposure to hydrogen peroxide.